2022
DOI: 10.1002/ar.24892
|View full text |Cite
|
Sign up to set email alerts
|

First occurrence of Psammophis (Serpentes) from Europe witnesses another Messinian herpetofaunal dispersal from Africa – biogeographic implications and a discussion of the vertebral morphology of psammophiid snakes

Abstract: We here describe abundant new snake material from the late Miocene (MN 13) of Salobreña, Spain. Vertebral morphology suggests a referral of the specimens to the extant psammophiid Psammophis, documenting the first occurrence of this genus in Europe. The diversity and disparity across the vertebral morphology of different psammophiid genera are discussed. We identify vertebral features that could diagnose Psammophis and therefore enable the recognition of the genus in the fossil record. A comparison of the new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…In the Vipera ammodytes and V. aspis fossils, the zygosphene possesses three distinct lobes, and the pre‐zygapophyseal processes are extremely short (Szyndlar, 1991). In the dorsal view of the trunk vertebra of Psammophis odysseus , the zygosphene possesses two distinct lateral lobes and a median lobe (Georgalis & Szyndlar, 2022). Loréal et al (2020) reported that in the trunk vertebrae of Colubrinae fossils, the zygosphenes appeared thin and exhibited a convex shape when viewed anteriorly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Vipera ammodytes and V. aspis fossils, the zygosphene possesses three distinct lobes, and the pre‐zygapophyseal processes are extremely short (Szyndlar, 1991). In the dorsal view of the trunk vertebra of Psammophis odysseus , the zygosphene possesses two distinct lateral lobes and a median lobe (Georgalis & Szyndlar, 2022). Loréal et al (2020) reported that in the trunk vertebrae of Colubrinae fossils, the zygosphenes appeared thin and exhibited a convex shape when viewed anteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…According to Szyndlar (1984), the classification of trunk vertebrae in the genus Natrix is based on a specific combination of characteristics, including elongated shape, sigmoid hypapophysis, well‐developed and rounded pre‐zygapophyseal processes, horizontally positioned pre‐zygapophyses, vaulted neural arches, and prominent neural spines. Georgalis and Szyndlar (2022) reported that the mid and posterior trunk vertebrae of Psammophis sp. lack hypapophyses.…”
Section: Discussionmentioning
confidence: 99%
“…Kurniawan et al [148] hypothesized that the earlier of these Psammophis immigration events occurred by dispersal across the Gomphotherium land bridge, and our biogeographic and divergence time results were consistent with this hypothesis (figure 4). The importance of Psammophis fossils from the Late Miocene of Spain [150]-where the genus does not presently occur-in understanding when and how ancestors of extant Psammophis lineages arrived in Asia is not clear.…”
Section: Das Et Almentioning
confidence: 99%
“…Kurniawan et al [154] hypothesized that the earlier of these Psammophis immigration events occurred by dispersal across the Gomphotherium land bridge, and our biogeographic and divergence time results were consistent with this hypothesis (figure 4). The importance of Psammophis fossils from the Late Miocene of Spain [156]-where the genus does not presently occur-in understanding when and how ancestors of extant Psammophis lineages arrived in Asia is not clear.…”
Section: Faunal Exchanges Between Africa and Eurasiamentioning
confidence: 99%